Respuesta :

Answer:

The series converges to [tex]\dfrac{1}{3}[/tex]

Step-by-step explanation:

It seems to be this series:

[tex]$ \sum_{n=1}^{\infty} \left(\dfrac{1}{2} \right)^{2n}$[/tex]

We have

[tex]$ \sum_{n=1}^{\infty} \left(\dfrac{1}{2} \right)^{2n} = \sum_{n=1}^{\infty} \left(\dfrac{1}{4} \right)^{n}$[/tex]

Using the Root test we can see that this series converges once

[tex]$ \lim_{n \to \infty} \sqrt[n]{|a_n|} < 1 \implies \sum_{n=1}^{\infty} a_n \text{ is convergent}$[/tex]

Then, [tex]$\lim_{n \to \infty} \sqrt[n]{\left(\dfrac{1}{4} \right)^{n}} = \lim_{n \to \infty} \dfrac{1}{4} = \dfrac{1}{4} < 1$[/tex]

The series is convergent.

Once the series is geometric, the first term is [tex]\dfrac{1}{4}[/tex] and the ratio is also [tex]\dfrac{1}{4}[/tex] in this case.

The sum of infinite geometric series is [tex]S = \dfrac{a_1}{1-r}[/tex] such that [tex]r < 1[/tex]

[tex]\therefore S = \dfrac{\frac{1}{4} }{1-\frac{1}{4}} = \dfrac{1}{3}[/tex]

ACCESS MORE